How woman-centred care is experienced and understood in maternity services by women and professionals: A rapid review - Gregory, Soma; Caffrey, Louise; Daly, Deirdre; Sheaf, Greg (Wiley, 2025)
Background: Woman/person-centred care is a key policy objective for maternity services in many high-income countries, both strategically and in terms of service delivery. This approach to care prioritises the individual woman's needs and aspirations over those of professionals or institutions. However, the concept remains ambiguous and practical implementation guidelines are lacking, leading to concerns that it is being practised tokenistically. Aim: To explore how woman-centred care in maternity services in high-income countries is experienced and understood by women and professionals. Methods: A rapid review was conducted to synthesise evidence on woman-centred care from women's and clinicians' per- spectives. Five bibliographic databases, CINAHL, Maternity and Infant Care, MEDLINE, PsycINFO and Web of Science, were searched systematically in December 2023. Citations eligible for inclusion were peer-reviewed quantitative, qualitative and mixed-methods empirical studies conducted in high-income countries and literature reviews reporting on studies conducted in high-income countries. Title and abstract screening, full-text screening, data extraction and quality appraisal were performed, with 10% of records double-screened to ensure consistency and minimise bias. Methodological quality was assessed using the Mixed Methods Appraisal Tool. Extracted data were synthesised thematically. Findings: In total, 5295 records were retrieved; after deduplication, 2707 records were screened, and 24 studies met the inclusion criteria. The review identified inconsistencies in how woman-centred care was experienced and understood at all levels of service provision, from policy directives to institutional practices. Diverse understandings of woman-centred care among stakeholders were found to influence interactions. Several studies revealed that professionals' varying interpretations affected their attitudes and approaches to care, while some women were found to hold differing expectations about woman-centred care provision. Conclusion: To realise the policy intention of woman-centred care, further context-specific investigations are needed to provide evidence and evaluation to inform implementation strategies.
PUBLISHED
Keywords: maternity care policy; maternity services; maternity services high-income countries; midwifery; person- centred care; rapid review; woman- centred care; BIRTH; CHILDBIRTH; Maternity Care; PREGNANCY; Person-centred care; Woman-centred care